The literature review of the governance frameworks in health system - Anthony, N. T. R.; Abdul Manaf, Rosliza; Lai, P. C. (Macrothink Institute, 2019)
Introduction: Governance in the health system refers to a range of decision making, and implementation undertakings conducted by decision-makers as they find ways to achieve national health policy objectives that are favourable to each country's health system. Currently, there are different types of frameworks that have been developed and these frameworks try to operationalize and assess how principles of governance at different levels of a health system are administered. While a number of frameworks for assessing governance in the health sector have been proposed, their application is often constrained by impractical indicators that are often not well-grounded, resulting in limited pragmatic work on governance in the health systems itself.Methods: Adopting a scoping review method, articles were identified using these databases namely BMC, Emerald, Elsevier, PubMed, Science Direct, Sage, Springer, Taylors & Francis, WHO and Wiley. Only articles written and published in English from 2009 to 2019 were included.Results: 5 of the frameworks have actually been tested and operationalized in practice from the 13 identified and reviewed frameworks that are largely theoretically based.Conclusion: A multitude of frameworks to assess health systems governance exist, however, there are not many examples of their application in the literature and healthcare systems with well-grounded proven results. Consequently, to facilitate a more comprehensive assessment and peruse of governance frameworks in health systems, the health system should have clear goals with continuous and committed support by accountable decision-makers pivoted by principles of good governance.